'n Klein lewe - Adriaanse, Wilhelmina (Department of English Language and Literature, 2014)
The retrospective story of a white middle-aged woman in South Africa born in the late 1950s, the novel traces, amongst other things, the development of her political consciousness from her early years as the daughter of a farmer in the Kalahari. Being a so-called 'little history' the story relates her exposure to other races during a time of strict division, important incidents such as a visit by the notorious Hendrik Verwoerd, the deaths of family members, a move to the Western Cape and the effects of growing up in a sternly Nationalist and Calvinistic household. The novel strives to portray the life of a woman locked into the constraints of a society burdened with restrictions, but who always keeps a keen and wary eye on 'homeland' policies, the expat generation, motherhood and life in Africa, etc., always filtered through the precarious discourse of whiteness.